Potensi Anti Bakteri Hard Candy Ekstrak Asam Jawa (Tamarindus indica L.) dengan Minyak Sereh Wangi (Oleum Citronellae) - Saptawati, Tunik; Handayani, Dwi Nurul; Gloria, Fransisca; Suwarni, Sri (Jurnal Farmasi & Sains Indonesia, 2023)
Tamarind and Sereh wangi (Citronellae winterianus Jowitt) are widely planted in Indonesia. Citronella oil is widely used as an anti-bacterial because of its secondary metabolite content. This study aims to determine the anti-bacterial potential of hard candy with active ingredients of tamarind extract and citronella oil. Tamarind fruit extract was prepared by maceration method using 96% ethanol solvent. Hard candy is made in 3 formulas with tamarind extract and citronella oil 0,1% (F1), citronella oil 0,2% (F2), and citronella oil 0,2% (F3). Antibacterial activity of hard candy examined using the disc diffusion method by measuring the diameter of the inhibition zone for the growth of Staphylococcus aureus and Escherichia coli bacteria. The result of the diameter of the inhibition zones F1, F2, and F3 for Escherichia coli were 4.25, 4.38, and 5.35 mm, respectively. The the diameter of the inhibition zones F1, F2, and F3 for Staphylococcus aureus were 2.30, 2.67 and 2.90 mm, respectively . It was showed that hard candy with active ingredients of tamarind extract and citronella oil was able to inhibit the growth of bacteria. The difference in the diameter of the inhibition zone between the formulas was analyzed using One Way Anova. The significance value is <0.05, so there is a significant difference in anti-bacterial activity between formulas. The concentration of citronella oil influence on antibacterial activity where the greater the concentration of citronella oil, the antibacterial activity to Staphylococcus aureus and Escherichia coli will increase. Keywords: Citronella oil, Tamarind, Hard Candy, Antibacterial.